Sinergitas Guru Al-Qur’an Hadis Dan Orang Tua Dalam Kegiatan Belajar Mengajar Siswa Di MTS Al-Ikhlas Membang Muda - Shofiyah Nabilah; Mahariah; Zulfiana Herni (CV. ITTC INDONESIA, 2025)
This research is entitled synergy of Al-Qur’an Hadist teachers and parents in student teaching and learning activities at Mts Al-Ikhlas Membang Muda. This research aims to find out what the form of synergy between Al-Qur’an Hadist Teachers and parents is in student teahing and learning activities and the obstacles. This research uses a qualitative research method with a phenomenological approach. The data collection technique is observation, interviews, and document study. The data analysis technique involves reducing data, presenting data, and drawing conclusions. The results of this research reveal that 1) the synergy of Al-Qur’an Hadist teachers and parents in improving student learning outcomes at Mts Al-Ikhlas Membang Muda has gone quite well. This is due to good communication via whatshapp.2) The inhibiting factors for the synergy of Al-Qur’an Hadist and parents in improving student learning outcomes at Mts Al-Ikhlas Membang Muda are one of the parents life demands so they rarely come to the madrasah, the attitude of parents who cannot be communicated with due to their busyness, as well as economic factor that do not have an internet quota so they cannot be contacted via whatshapp.